2000
DOI: 10.1086/312463
|View full text |Cite
|
Sign up to set email alerts
|

The Density Profiles of the Dark Matter Halo Are Not Universal

Abstract: We perform a series of high-resolution N-body simulations designed to examine the density profiles of dark matter halos. From 12 simulated halos ranging in mass from 2x1012 to 5x1014 h-1 M middle dot in circle (represented by approximately 1 million particles within the virial radius), we find a clear systematic correlation between the halo mass and the slope of the density profile at 1% of the virial radius, in addition to the variations of the slope among halos of similar mass. More specifically, the slope i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
437
7
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(482 citation statements)
references
References 24 publications
37
437
7
1
Order By: Relevance
“…In the outer region, the density proÐles are very similar for all runs. The dependence of the power-law index of the inner cusp on halo mass observed by Jing & Suto (2000) was not reproduced in our simulations. In the following subsections we discuss the self-similar growth of the halo (°3.4), the universality of the proÐle (°3.5), and the mechanism for selfsimilar growth (°3.6).…”
Section: Other Numerical E †Ectscontrasting
confidence: 58%
See 1 more Smart Citation
“…In the outer region, the density proÐles are very similar for all runs. The dependence of the power-law index of the inner cusp on halo mass observed by Jing & Suto (2000) was not reproduced in our simulations. In the following subsections we discuss the self-similar growth of the halo (°3.4), the universality of the proÐle (°3.5), and the mechanism for selfsimilar growth (°3.6).…”
Section: Other Numerical E †Ectscontrasting
confidence: 58%
“…Moore et al (1998Moore et al ( , 1999 and Ghigna et al (2000) performed simulations with up to 4 ] 106 particles and obtained results similar to ours. They found that cluster-sized halos also have steeper cusps than those in the NFW proÐle, and they proposed a modiÐed universal proÐle : o \ o 0 /M(r/r s )1.5 ] On the other hand, Jing & Suto (2000) [1 ] (r/r s )1.5]N. found that the density proÐle of dark matter is not universal. They performed a series of N-body simulations and concluded that the power of the cusp depends on mass.…”
Section: Introductionmentioning
confidence: 99%
“…Replacing M v in equation 8, the virial radius is found to be R v = 12 kpc. Using the relationship between M v and the concentration parameter c found in [37] (see also [38]) yields c ≃ 22. Finally r s = 5.35 × 10 −1 kpc is obtained using r s = c/R v .…”
Section: Astrophysical Factor Calculationmentioning
confidence: 91%
“…Within the cold dark matter (CDM) paradigm, ⋆ E-mail: sebastien.peirani@oca.eu earlier works ignoring the effects of gas dissipation and star formation processes, have suggested that dark matter haloes have spherically-averaged density profiles that can be well fitted by simple analytical function such as the NFW profile (Navarro et al 1996a;Navarro et al 1997) in which the inner slope tends to -1 or could even be as steep as -1.5 (e.g. Moore et al 1998;Jing & Suto 2000). Later numerical works favour the Einasto profile with a finite central density though this profile is still cuspy and close to the NFW one (Merritt et al 2006;Stadel et al 2009;Navarro et al 2010).…”
Section: Introductionmentioning
confidence: 99%